One-Step Fabrication of Enzyme-Immobilized Reusable Polymerized Microcapsules from Microfluidic Droplets - Varshney, Rohit (ACS Omega, 2019)
[Image: see text] Enzyme immobilization is an essential prerequisite for biocatalysis. In this context, emulsion provides an excellent template for assembling enzymes at the oil–water interface. A microfluidic approach has been adopted to produce oil-in-water-type emulsions stabilized by gold nanoparticle–catalase conjugates. In situ ring-opening polymerization of the oil phase produces solid core enzyme-immobilized microcapsules (MCs). These resultant MCs exhibited a K(m) value of 42 mM and shows 1.1-fold higher activity compared to free enzymes. Finally, the robust MCs showed excellent recyclability, which can meet the demand of industrial biotechnological applications.